ASET SEBAGAI SUBJEK HUKUM DALAM UPAYA PENGEMBALIAN KERUGIAN KEUANGAN NEGARA PADA TINDAK PIDANA KORUPSI - Achmad Rilyadi Sholeh; Setiawan Noerdajasakti (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Corruption is a problem that results in high financial and economic losses in Indonesia. UNCAC has launched recommendations for countries to make arrangements regarding Non-Conviction Based asset Forfeiture (NCB) since 2003 which aims to recover maximum state financial losses. This is based on the fact that the state losses recovered are not proportional to the state financial losses incurred due to corruption crimes. The research used is normative juridical with a statutory approach, conceptual approach, and comparison with other countries. The conception of assets as legal subjects in the NCB is based on the theory of legal fiction where assets in their position as legal subjects make them seem "guilty" when the way of use or the process of obtaining them is against the law. Assets in this case are considered to be able to perform a legal act that can be accounted for as happened in several cases in the United States, the Philippines, Thailand, not to mention Indonesia. Thus, because it focuses on the "fault" of the object, asset forfeiture can still be carried out even though the object or asset has changed hands. Legislation in Indonesia has actually adopted the concept of NCB, but it does not fulfill the basic essence of the concept where the goal is to recover state losses arising from corruption maximally and quickly. Therefore, laws governing asset forfeiture must be made specifically to accommodate this, one of which is through the bill on asset forfeiture.